Alex and the hobo : a Chicano life and story - Taylor, José Inez, 1937- (University of Texas Press, 2003)
When a ten-year-old boy befriends a mysterious hobo in his southern Colorado hometown in the early 1940s, he learns about evil in his community and takes his first steps toward manhood by attempting to protect his new friend from corrupt officials. Though a fictional story, Alex and the Hobo is written out of the life experiences of its author, José Inez (Joe) Taylor, and it realistically portrays a boy's coming-of-age as a Spanish-speaking man who must carve out an honorable place for himself in a class-stratified and Anglo-dominated society. In this innovative ethnography, anthropologist James Taggart collaborates with Joe Taylor to explore how Alex and the Hobo sprang from Taylor's life experiences and how it presents an insider's view of Mexicano culture and its constructions of manhood. They frame the story (included in its entirety) with chapters that discuss how it encapsulates notions that Taylor learned from the Chicano movement, the farmworkers' union, his community, his father, his mother, and his religion. Taggart gives the ethnography a solid theoretical underpinning by discussing how the story and Taylor's account of how he created it represent an act of resistance to the class system that Taylor perceives as destroying his native culture.